Pengaruh Jenis Pemanis yang Berbeda terhadap Sifat Kimia Kopi Lengkuas - Destryana, R. Amilia; Yuniastri, Ratih; Wibisono, Aryo (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2019)
Galangal coffee is a local agricultural commodity food product in Sumenep Regency. This product is produced based on the preference of people for coffee drinks. Galangal coffee is a mixture of coffee powder and galangal powder which has a different aroma and taste. The use of sugar as an additional ingredient in galangal coffee product is used to increase product quality in the composition of nutrients, storability, and health effects on the body. Sweetener commonly used in food products is sucrose, such as cane sugar, palm sugar, and corn sugar which are sweeteners but have a lower glycemic index than cane sugar. The purpose of this study was to determine the effect of the use of sweetener: cane sugar, palm sugar and corn sugar on the chemical properties of galangal coffee product. The design used in this study is a completely randomized design (CRD) non-factorial pattern with 3 replications. The method used is an experimental method of chemical parameters: carbohydrate content, water content, fat content, protein content, and ash content. Result of ANOVA at a significance level of 5% showed that the use of different types of sweeteners significantly affected total carbohydrate content, water content, ash content, and fat content. The parameter values ??of the chemical properties of the product in this study were: carbohydrate content of 64.47-82.60%, the water content of 5.19-17.08%, the ash content of 1.74 - 4.17%, fat content of 3.25 - 6.79%, and protein content from 4.96 to 7.5%.